(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Mr. Narendra Modi, the Prime Minister of India, has been in news for his movements abroad and creating an effect by his super encourages while addressing individuals of Indian origin. Numerous observers have endeavored to contrast his one year in office and that of Dr. Manmohan Singh who was the Prime Minister of India for 10 years. In 2014 India casted a ballot for Mr. Narendra Modi who offered a thoroughly contrasting style of leadership to the general population of India. This article makes an endeavor to analyze the leadership styles of Mr. Narendra Modi and Dr. Man Mohan Singh using distributed research on leadership styles.